LEGISLATION PROCEDURE FOR THE FORMATION OF REGIONAL REGULATIONS IN CIREBON REGENCY - Moeryani, Dwi; Pratama, Rio Nouval; Kurniawan, Chandra Adithiya; Numbers, Nuraeni (Ann Publisher, 2025)
Abstract Background. Regional Regulations (Perda) have a very important role in the process of development and regulation of people's lives at the regional level. The realization of an effective Regional Regulation in accordance with local needs is highly dependent on the existence of clear and transparent procedures. Purpose. This study aims to find out how the procedure for forming regional regulations in Cirebon Regency is, focusing on the stages passed, the challenges faced, and the role of the community in the process. Method. In this study, we used a qualitative approach by collecting data through interviews, observations, document analysis, and studies of related government policies. Result. The results of the study show that the process of forming regional regulations in Cirebon Regency consists of several steps, namely planning, drafting, discussion, and ratification. Conclusion. Although there are procedures that have been set, there are still obstacles such as lack of socialization and community participation which are challenges in its implementation. Implementation. These findings also highlight the importance of increasing transparency and accountability at every stage of regional regulation formation so that the public can have more trust in local governments.